Estimation of Genetic Parameters in Teak (Tectona grandis) without Raising Progeny - Kepharnath, S.; Chetty, C. K. Ramanatha; Rawat, M. S. (Indian Forester, 1969)
Estimation of genetic parameters is very important in tree breeding work. Classical methods in use to estimate genetic variances for tree species involve raising progeny and this is obviously time consuming. Shrikhande (1957) developed a method which does not necessitate raising of progeny and he applied the same to Coconut palm populations. His method has been expanded by Sakai and Hatakayama (1963) to estimate genetic covariances which lead to estimating genetic correlations. In this paper genetic correlation of stem girth and number of internodes has been estimated to be 0.90 for Teak (Tectona grandis) trees, which is a hardwood species of great economic importance. The efficacy of the method has also been tested by showing that in a seed propagated stand in a small compact area, environmental component of variation is negligible. Heritabilities for various tree characters were also estitnated and were found to be high thus indicating that considerable genetic gain can be achieved from selection.